Posttraumatic onychoheterotopia: A case and review of the pediatric literature. Issue 5 (2nd August 2021) - Braun, Mitchell; Reynolds, Sean; Shah, Sonal D.
Abstract: Background: Onychoheterotopia, or ectopic nail, is a rare nail condition in which nail growth occurs in areas other than the distal phalanges. The majority of cases in the literature are noted to be congenital; however, acquired cases have less commonly been described following either acute or chronic trauma. Methods: We present a case of acquired onychoheterotopia in a child, with a corresponding literature review of acquired pediatric onychoheterotopia cases for comparison. Results: There were a total of 10 cases of acquired onychoheterotopia in pediatric patients in the literature. Including our patient, 81.8% (9/11) developed an ectopic nail on the fingers. Crush injury preceded the ectopic nails in 45.5 % (5/11) of cases. Infection occurred in 27.3% (3/11). Conclusions: Although the incidence and prevalence of acquired onychoheterotopia are unknown, it seems to be an uncommon phenomenon. From our case and others from the literature, there may be associations with crush injury specifically. Further research will be needed to fully elucidate the pathophysiology and risk factors for ectopic nail growth.